2021
DOI: 10.15212/ijafr-2020-0147
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of robust animals for grass-based production systems

Abstract: A characterisation of dairy, beef and sheep breeds and/or strains best suited to profitable/sustainable production within the context of European [semi] intensive pasture-based systems is presented. To deliver optimal performance, pasture must be managed effectively, but pasture-based systems are less energy intensive, are climate sensitive and induce challenges and constraints not normally posed to animals in intensive feeding environments. This emphasises the importance of animal traits associated with robus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…When considering the selection of a breed for an organic system, special attention should be paid to the breed's genetic traits and selection indexes. Due to the nature of organic production, there is the need for animals to be hardy and suitable for grazing on outdoor pasture systems [102]. Currently, most countries do not use a separate performance evaluation system for organic animals.…”
Section: Breedingmentioning
confidence: 99%
See 1 more Smart Citation
“…When considering the selection of a breed for an organic system, special attention should be paid to the breed's genetic traits and selection indexes. Due to the nature of organic production, there is the need for animals to be hardy and suitable for grazing on outdoor pasture systems [102]. Currently, most countries do not use a separate performance evaluation system for organic animals.…”
Section: Breedingmentioning
confidence: 99%
“…However, the use of insemination with semen from non-organic bulls is allowed, and thus these bulls can come from embryo transfer. Delaby et al [102] has shown that the complete exclusion of the linkage of multiple ovulation and embryo transfer (MOET) to organic production would result in a significantly large loss in genetic gain in organic population.…”
Section: Breedingmentioning
confidence: 99%
“…The descriptive data are presented in Table 1. 9 PUFA/SFA ratio: polyunsaturated fatty acid/saturated fatty acid ratio; 10 ω-6/ω-3 ratio: n-6/n-3 PUFA ratio; 3,5,6,7,8,9,10 data based on 30 animals.…”
Section: Carcass Grading and Muscle-cut Collectionmentioning
confidence: 99%
“…For instance, the marbling level of “abundant” corresponds to the grade of “prime” in the United States Department of Agriculture (USDA) beef-grading system. Specific crossbreeding with early-maturing breeds to enhance fat synthesis and deposition is a way to take advantage of grass feeding systems in order to produce meat of good eating quality [ 9 ]. Hardy breeds, such as Salers, are well adapted to the mountainous pasture environment, unlike more specialized beef breeds (i.e., Angus).…”
Section: Introductionmentioning
confidence: 99%